Tumor-to-Tumor Metastasis of Prostatic Adenocarcinoma in Transitional Meningioma: A Case Report and Literature Review - Rafael Harter Tomaszeski; Luiz Roberto Tomasi Ribeiro; Deborah Lumi Shuha; Luiza Ribeiro; Eduardo Cambruzzi; Marcelo Neutzling Schuster; Marcos Dalsin; Ericson Sfreddo; Paulo Valdeci Worm (Brazilian Neurosurgery, 2025)
Benign and malignant tumors can be receivers of tumors from other sites. Intracranial prostate metastasis is a rare phenomenon. Implantation of prostate metastasis in a meningioma is an exceptional condition. The article presents a case of metastasis of prostatic adenocarcinoma implanted in a transitional meningioma of the left frontal convexity, in which the patient began with neurological symptoms and had no previous diagnosis of prostate neoplasia.